Functional kaurene-synthase-like diterpene synthases lacking a gamma domain are widely present in Oryza and related species. Issue 9 (9th July 2021) - Itoh, Akira; Nakazato, Shinta; Wakabayashi, Hiroki; Hamano, Ayame; Shenton, Matthew R; Miyamoto, Koji; Mitsuhashi, Wataru; Okada, Kazunori; Toyomasu, Tomonobu
ABSTRACT: Various diterpene synthases have been functionally identified in cultivated rice ( Oryza sativa ). These are the homologs of ent- copalyl diphosphate ( ent- CDP) synthase and ent- kaurene synthase (KS) that are responsible for the biosynthesis of gibberellins, diterpenoid phytohormones. We isolated a cDNA encoding full-length OsKSL12, a previously uncharacterized KS like (KSL) enzyme that consists of a β-domain and an α-domain with an active center, but lacks an N-terminal γ-domain. Functional analysis using a bacterial expression system showed that recombinant OsKSL12 converted ent- CDP into ent- manool or ent -13- epi -manool. Comparative genomics revealed that functional OsKSL12 homologs exist in diverse wild species in the Oryzeae— Oryza nivara ( Oryza rufipogon ), Oryza coarctata, Oryza granulata, Leersia perrieri, and Leersia tisseranti . KSL12 homologs in O. granulata, L. perrieri, and L. tisseranti preferentially reacted with geranylgeranyl diphosphate rather than ent -CDP, resulting in geranyllinalool rather than ent -manool or ent -13- epi -manool as the main product, meaning that KSL12 functionally diversified during evolution in the Oryzeae. Graphical Abstract: